2014
DOI: 10.21608/ejabf.2014.2204
|View full text |Cite
|
Sign up to set email alerts
|

Qarun Lake fisheries; Fishing gears, Species composition and Catch per unit effort

Abstract: Qarun Lake is a closed salty basin located about 90km southern Cairo Egypt, cover an area of 230km 2 with annual production of about 3000 tonnes. The present study assessed the lake fishery for better management purpose. Data, information and samples were collected through 42 field trips and 311 fishermen interviews during fishing season (2010-2011). The lake was divided into three sub-areas, east, middle and west. It was found that the fishing gears used in the lake were; 1-Trammel nets with four types differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…The commercial total annual catch decreased from 4000 tonnes during 1920 to an average of 1-2 thousand tonnes in subsequent years (El-Serafy et al, 2014).…”
Section: Fishing Boats and Methodsmentioning
confidence: 97%
See 4 more Smart Citations
“…The commercial total annual catch decreased from 4000 tonnes during 1920 to an average of 1-2 thousand tonnes in subsequent years (El-Serafy et al, 2014).…”
Section: Fishing Boats and Methodsmentioning
confidence: 97%
“…2-Seine nets with three types and targeting M. cephalus, anchovy and shrimp. 3-Others fishing methods (Fishing aggregation system, traps and hooks) targeting mainly T. zillii (El-Serafy et al, 2014). Krzebietke et al, (2016) reported that, the main fishing equipment used in the lake was trammel nets, beach seines, hand lines and traps.…”
Section: Fishing Boats and Methodsmentioning
confidence: 99%
See 3 more Smart Citations